Determinant of Transfer Pricing Practices for Property and Real Estate Companies Listed on The Indonesia Stock Exchange period 2020-2022 - Marcella, Vicky; Hutahaean, Thomas Firdaus; Tua Pandiangan, Saut Maruli (IPM2KPE, 2024)
This study aims to examine the effect of the Audit Committee, Audit Quality, Firm Size and Profitability on Transfer Pricing (Case Study on Companies Listed on the Indonesia Stock Exchange, Property and Real Estate Sub-Sector, 2020-2022 Period). The researcher used a quantitative research method. The population used in this study was 91 Property and Real Estate companies and a sample of 15 Property and Real Estate companies with a total of 45 observations. The data analysis technique used multiple linear regression analysis with SPSS version 27. The results of the study showed that. The Audit Committee has a positive and significant effect on Transfer Pricing on. Audit Quality, Firm Size and Profitability do not affect Transfer Pricing in Companies Listed on the Indonesia Stock Exchange, Property and Real Estate Sub-Sector, 2020-2022 Period. Conclusion, the Audit Committee is an important factor in influencing decisions related to Transfer Pricing in Property and Real Estate sub-sector companies. Keywords: Firm Size, Profitability, Audit Committee, Audit Quality, Transfer Pricing